Perilunate Carpal Dislocation: A Case Report - Camargo, Carlos Eduardo Seganfredo; Coberllini, Luigi Dal Pizzol; Fernandes, Matheus Guanabara; Guanabara, Rafael Oselame (Brazilian Journal of Case Reports, 2025)
Perilunate dislocations of the wrist occur due to instability in the ligaments that stabilize the carpal bones relative to each other. Despite their low incidence, these injuries are highly severe. The aim of this study is to report a case in which it is possible to demonstrate the trauma mechanism, clinical presentation, diagnosis, treatment, and follow-up. The patient is a male with a history of trauma from a fall, diagnosed with perilunate dislocation of the wrist through physical examination and imaging, requiring surgical treatment to restore carpal anatomy. It is concluded that accurate identification and diagnosis of the injury, as well as selection of the appropriate treatment, are essential for preserving limb function and preventing future complications, such as carpal instability, local fibrosis, carpal osteoarthritis, and avascular necrosis.